Keterampilan Membaca Dalam Pembelajaran Bahasa Arab - Dian Febrianingsih (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2021)
Reading is a language skill that is no less important than other language skills. Reading skill is a subject that has many opportunities to be developed. Reading materials are widely available in various fields of science, reading activities can also be carried out anywhere and anytime. Based on this, reading skills are one of the focuses in foreign language learning orientation, and Arabic is no exception. Arabic reading skills are a skill that must be mastered by students with the aim of developing Arabic language skills. The purpose of learning reading skills is to train students to be more skilled and fluent in reading comprehension and develop students' reading skills. The method used in learning Arabic must be able to increase the interest of the students to be happy in learning to read Arabic. Reading skills in learning Arabic include the understanding of reading skills, methodologies for teaching reading skills, reading patterns, stages in reading, reading difficulties and improving Arabic reading skills. The writing of this article uses the library research method. The data used are sourced from books, articles and several other sources and/or information deemed relevant to the study theme.